Ice Breaker Effectiveness for Increasing Students' Interest in Learning English - Mardiani, Mardiani (PT. Riset Press International, 2024)
English teachers are required to have the ability to plan, organize, and evaluate English learning effectively. English should also be fun for students because it can be a factor in making them enthusiastic. Ice-breaking is one of the methods used to increase students' interest in learning English. This research aimed to analyze the impact that occur to students after the application of the icebreaker method. This research was conducted using mixed-methods research at SMA Muhammadiyah 5 Makassar in the academic year 2023-2024. This research used 31 samples from class X MIA. The research instruments were questionnaires, note-taking, recording, and interview questions. The results showed that the impacts after the application of the icebreaker method were: increasing students' knowledge; making students more diligent; stimulating creativity; increasing vocabulary; and motivating students. The score of the questionnaire before treatment was 12,89%, and the score of the questionnaire after treatment was 19,01. Thus, it could be argued that students' interest could be increased through the use of ice breaker. This research can be useful for English teachers to improve their understanding of students' problems, increase students' interest in learning, identify their problems, and solve their problems in learning English.